2018
DOI: 10.3389/fimmu.2018.01451
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Leukocytes by TspanC8 Tetraspanins and the “Molecular Scissor” ADAM10

Abstract: A disintegrin and metalloproteinase 10 (ADAM10) is a ubiquitous transmembrane protein that functions as a “molecular scissor” to cleave the extracellular regions from its transmembrane target proteins. ADAM10 is well characterized as the ligand-dependent activator of Notch proteins, which control cell fate decisions. Indeed, conditional knockouts of ADAM10 in mice reveal impaired B-, T-, and myeloid cell development and/or function. ADAM10 cleaves many other leukocyte-expressed substrates. On B-cells, ADAM10 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 66 publications
0
26
0
Order By: Relevance
“…The TspanC8s comprise Tspan5, 10, 14, 15, 17 and 33, and are so-called because of eight cysteines within their large extracellular loop. Different cell types express distinct TspanC8 repertoires (9,10) and emerging evidence suggests that each TspanC8 may cause ADAM10 to cleave specific substrates (6,(11)(12)(13)(14)(15)(16). However, there is an urgent need to generate monoclonal antibodies (mAbs) to all TspanC8s, to define fully their expression profiles and functional mechanisms.…”
mentioning
confidence: 99%
“…The TspanC8s comprise Tspan5, 10, 14, 15, 17 and 33, and are so-called because of eight cysteines within their large extracellular loop. Different cell types express distinct TspanC8 repertoires (9,10) and emerging evidence suggests that each TspanC8 may cause ADAM10 to cleave specific substrates (6,(11)(12)(13)(14)(15)(16). However, there is an urgent need to generate monoclonal antibodies (mAbs) to all TspanC8s, to define fully their expression profiles and functional mechanisms.…”
mentioning
confidence: 99%
“…ADAM10 is a transmembrane protease that cleaves extracellular regions of several transmembrane target proteins, including Notch . Furthermore, other Tspans have been shown to regulate ADAM10 maturation and activity, and Tspan3 itself has been shown to regulate ADAM10 expression . Our studies show that the Cldn‐11 effect on Notch signaling may be mediated via Tspan3 regulation of ADAM10 function.…”
Section: Discussionmentioning
confidence: 66%
“…ADAM10 is a transmembrane protein that cleaves extracellular regions of several transmembrane target proteins, including Notch, and we previously showed that osteoblasts express ADAM10 . Further, it was recently found that mutation of Tspan14 reduced ADAM10 surface expression and activity in human umbilical vein endothelial cells, and a number of other Tspans, including Tspan5, Tspan10, Tspan15, Tspan17, and Tspan33, have been shown to regulate ADAM10 activity . Notably, Tspan3 has also been found to regulate ADAM10 expression .…”
Section: Resultsmentioning
confidence: 93%
“…Due to the ease and simplicity of sample handling, QPM techniques can aid predictive models of thrombus formation, contraction, and stability across a range of shear rates and are ideal modalities for development for point-of-care devices to assess platelet function and thrombosis and bleeding risk in at risk patients. These imaging approaches can address research questions targeting mechanisms involved in the regulation of thrombus size, for example the respective roles of metalloproteinases (34,198) or tetraspanins (199,200) in modulating thrombus size and stability. However, as QPM techniques rely on phase information in transmitted light, they can often be limited by strongly scattering media.…”
Section: Beyond Fluorescence Imaging: Quantitative Imaging Without Flmentioning
confidence: 99%